2020
DOI: 10.1007/s42452-020-2761-9
|View full text |Cite
|
Sign up to set email alerts
|

A first approach on the assessment of the creep behavior of MoTaNbVxTi high entropy alloys by indentation testing

Abstract: MoTaNbV x Ti refractory high entropy alloys were tested with dynamic indentation technique in order to assess their creep behavior. The loading rate was kept constant and three indentation depths were applied. It was found that, by increasing the indentation depth and the V content of the alloys, the stress exponent was reduced. This reduction was associated with the maximum applied stress at the peak load before the holding period and the increase of lattice distortion parameter with increasing the V content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 17 publications
9
10
0
Order By: Relevance
“…One final observation that must be mentioned is the fact that serrations, if present, are found in most of the cases associated with the lower loading speeds. This observation is in agreement with other experimental efforts [5][6][7][8][9][10][11]22], according to which the most important factor influencing the formation of serrations is the strain rate. Various research efforts have shown that high strain rates during the loading stage result in the absence of serrations, i.e., lack of creep deformation during loading [5][6][7][8][9][10][11].…”
Section: Creep Assessmentsupporting
confidence: 93%
See 3 more Smart Citations
“…One final observation that must be mentioned is the fact that serrations, if present, are found in most of the cases associated with the lower loading speeds. This observation is in agreement with other experimental efforts [5][6][7][8][9][10][11]22], according to which the most important factor influencing the formation of serrations is the strain rate. Various research efforts have shown that high strain rates during the loading stage result in the absence of serrations, i.e., lack of creep deformation during loading [5][6][7][8][9][10][11].…”
Section: Creep Assessmentsupporting
confidence: 93%
“…This is expected since the more prolonged the time, the more time for the available dislocations to move and provide plastic flaws, i.e., plastic deformation. Similar observations can also be found in other experimental efforts [8,9,22].…”
Section: (2) Net Creep Deformation (H Creep )supporting
confidence: 90%
See 2 more Smart Citations
“…This means that the deformation rate, in turn, does not show much dependence on the applied load, and as such, the stress exponent decreases. Based on the literature [170,173,174,227], these calculated values are attributed to dislocation sliding as the dominant mechanism concerning the dislocation movement, while for higher values, dislocation climbing plays also a supportive role.  In the case of the eutectic micro-constituent, the formulation of a mechanism that would explain the changes in the stress exponent values is very tricky.…”
Section: Stress Exponent Analysismentioning
confidence: 96%